UNVEILING HANNA SCHMITZ: A SOCIOCULTURAL ANALYSIS OF MORALITY, GUILT, AND MEMORY IN BERNHARD SCHLINK'S THE READER - Bakr, Mahir Ahmed; Abdul, Zanyar Kareem; Alipour, Ahdiyeah (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
This paper, titled "Unveiling Hanna Schmitz: A Sociocultural Analysis of Morality, Guilt, and Memory in Bernhard Schlink's The Reader," explores the enigmatic character of Hanna Schmitz by examining her moral decisions, guilt, and the influence of societal norms. Through an in-depth analysis, it delves into the complexities of identity formation, memory, and the aftermath of historical trauma, offering insights into the human condition. The study reveals the external factors and internal motives behind Hanna Schmitz's involvement in the Holocaust, following a sociocultural analysis of various aspects that entangle the main character in the consequences of her choices, ultimately leading to her suicide. The analysis highlights how literacy and education can become destructive tools when wielded by ignorant and arrogant elites to segregate and manipulate. Hanna suffers from a societal disease that shapes her actions and fate. The paper argues that society and the tyrannical regime play pivotal roles in shaping Hanna's unfortunate destiny. Her struggle with illiteracy and her efforts to conceal it further underscore the societal pressures and personal conflicts she faces.